Wild Plants as Food for Communities Living Near The Arak-Arak Bondowoso Teak Forest - Fausiyah, Sefa; Hasanah, Rafiatul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
Indonesia's biodiversity offers great potential for the utilization of wild plants as alternative food sources. This study aims to inventory the types of wild plants utilized as food by communities around the Jati Arak-Arak Forest area in Bondowoso. The approach used is qualitative ethnography with purposive and snowball sampling techniques, as well as triangulation methods through participatory observation, in-depth interviews, and field documentation. The results of the study indicate that there are 20 wild plant species from 18 different families that are actively consumed by the local community, particularly the leaves, fruits, and stems. Scientific classification and morphological analysis reveal that these plants contain bioactive compounds such as flavonoids, vitamins, and antioxidants, supporting their functional value as food. The calculation of use value (UV) indicates that Diplazium esculentum (fern) and Colocasia esculenta (taro) have the highest value (UV = 1.00), indicating a high level of utilization. The utilization of these wild plants as food to meet the nutritional needs of the communities around the Arak-arak Teak Forest necessitates the preservation of local wisdom to ensure the sustainability of natural resources and cultural heritage.